"RIM" classification for prediction of sinkhole tragedy in limestone areas / Roslan Zainal Abidin … [et al.] - Zainal Abidin, Roslan; Jamalludin, Damanhuri; Arshad, Mohd Fadzil; Noordin, Muklis (Universiti Teknologi MARA, Perlis, 2003)
Sinkhole Is a costly recurring problem faced by many countries such as Malaysia where some of the areas having limestone bedrock with underground cavities. This research is to establish the relationship between soil grading characteristics and occurrence of sinkholes. Soil samples from sinkhole tragedy areas and areas where sinkholes were known to occur as well as areas where sinkholes are prone to occur, having limestone as the bedrock were taken and their grading characteristics identified. From the results, it can be seen that a pattern on the soil grading characteristics can be categorised or classified in relation to the sinkhole tragedy areas as well as to other areas having a similar pattern. The category of classifying the degree of sinkhole occurrence was named as "RIM" Classification for Sinkhole Failure (after the name of researchers, Roslan, Damanhuri, Mohd. Fadhil & Mukhlis) can be used to indicate the risk level of potential sinkhole occurrences. By using the "RIM" Classification, the prediction of sinkhole occurrences can easily be made by simply carrying out sieve tests to obtain the percentages of sand, silt and clay. These percentages are then compared with the "RIM" Classification to give an indication to the public as well as the government agencies on the degree of sinkhole occurrences on their land that can cause damage to their properties and lost of lives.